EU Proposals to Reform the Investor-to-State Dispute Settlement System – a Critical Analysis of Selected Issues Addressed in the Concept Paper “Investment in TTIP and Beyond – the Path for Reform” - Garnuszek, Anita; Orzeł, Aleksandra (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
The article deals with current proposals regarding the reform of the investor-to-state dispute settlement system (ISDS). At present, the European Union and the United States are involved in the negotiations regarding the Transatlantic Trade and Investment Partnership (TTIP). In this respect, the EU prepared the Concept Paper, in which it presented its ideas pertaining to the reform of investment arbitration and prospected provisions of TTIP dealing with the matter. The authors aim is to analyze the most important proposals included in the Concept Paper and make an assessment whether they should be regarded as beneficial for the system or potentially detrimental. The authors find some of the Commission’s proposals, including an idea to create an appellate mechanism, ensure third parties right to submit amicus curiae briefs and ideas pertaining to elimination of the risk of parallel proceedings to be potentially advantageous for ISDS as they can help to restore the balance between states and investors. To the contrary, the idea to enhance states’ right to regulate, preclude arbitrators from applying and interpreting domestic law and to change the current system of appointing arbitrators and in further perspective, creating an international court for investment disputes, is questionable and could lead towards weakening of investors protection which was traditionally the main purpose of ISDS.
Keywords: system rozstrzygania sporów między inwestorem a państwem (ISDS); reforma arbitrażu inwestycyjnego; Transatlantyckie Partnerstwo w dziedzinie Handlu i Inwestycji (TTIP)